Margin Requirements, Volatility, and the Transitory Component of Stock Prices - Hardouvelis, A. (American Economic Review, 2016)
Official margin requirements in the U.S. stock market were established in October 1934 to limit the amount of credit available for the purpose of buying stocks. Since then, higher or rising margin requirements are associated with lower stock price volatility, lower excess volatility, and smaller deviations of stock prices from their fundamental values. The results hold throughout the post-1934 period and are not very sensitive to the exclusion of the turbulent depression years from the sample. Thus margin requirements seem to be an effective policy tool in curbing destabilizing speculation. (JEL 313, 520). Federal regulation of securities margins was mandated by Congress in the Securities Exchange Act of 1934. The stock market experience of the late 1920s led Congress to the conclusion that credit-financed speculation in the stock market might create excessive market volatility through a pyramidingdepyramiding process.' Congress reasoned that the imposition of margin requirements could constrain the amount of borrowing and prevent excessive market volatility, and subsequently gave the Federal Reserve jurisdiction over the level of margin requirements. Since 1934, the Federal Reserve